REKONSTRUKSI PROFESIONALISME GURU SKI DALAM IMPLEMENTASI KURIKULUM MERDEKA BERBASIS PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - MUNAWIR; VANNESA DELLA PERMATA; RIZKA AMALIA (STKIP Subang, 2026)
The professionalism of teachers is essential for enhancing student learning results, especially in Islamic Cultural History (SKI) subjects in elementary schools. This study intends to analyze the development of SKI teacher professionalism through the implementation of the Merdeka Curriculum, which focuses on varied or different learning methods. Varied learning requires teachers to identify and cater to students’ different needs, including variations in skills, interests, backgrounds, and learning styles, so that every student can reach their best learning results.This research uses a qualitative method with a literature review approach, examining various relevant theories, earlier studies, and policy documents concerning teacher professionalism, the Merdeka Curriculum, and varied learning. The results show that teacher professionalism is shown not only in knowledge of the subject but also in teaching skills, flexibility, and ongoing self-improvement. SKI teachers need to be responsive to curriculum changes, especially the shift from the K13 curriculum to the Merdeka Curriculum, by creating adaptable, student-focused learning experiences.Moreover, effective strategies to improve teacher professionalism include using creative teaching approaches, contextual learning, and integrating technology-based resources to support interactive and meaningful learning. These strategies help teachers to better meet student diversity and encourage participation in SKI subjects. In the end, enhancing teacher professionalism greatly impacts the quality of learning and the achievement of educational objectives.